STUDY OF CHANGES IN ADSORPTION ACTIVITY FOR BENZENE IN COALS BASED ON WOOD WASTE (Scientific journal of the Fergana State University, 2023)
The article discusses methods for obtaining activated carbon adsorbents (AC) based on the waste of trunks of plane tree, ash, apricot, walnut, and cherry. It is important to use this type of adsorbents for the adsorption of foreign substances in the liquid and gas phases. For this purpose, AC adsorbents were prepared from the waste of trunks of plane tree, ash, apricot, walnut, and cherry growing on the territory of our republic and their physicochemical, colloidal properties were studied. For this, AC samples were taken using the methods of thermal and steam-gas activation of plant biomass. The adsorption of prepared samples by benzene vapors was studied. On the basis of adsorption isotherms and BET theory, indicators of the adsorption properties of samples (saturation adsorption, monolayer capacity, specific surface area) and their changes are explained in detail. The saturated adsorption volume and the volumes of AC meso- and micropores were determined on the basis of TOSM. In addition, the mean pore radius is shown. The mechanisms of adsorption and desorption processes are described, i.e., hypotheses related to the adsorption of the adsorbent on the adsorbent and the dependence of the adsorption value on the activation temperature. According to the results of benzene vapor adsorption of AC samples, the amount of adsorbed carbon adsorbent activated by water vapor for 1.5 hours at 800 °C (by pyrolysis under airless conditions) from maple stem waste was established, the residual pore volume was higher than the samples. These AC samples can be used as adsorbents for the purification of production products from organic compounds in various areas of the chemical industry.